ANALYSIS OF STEEL STRUCTURES BEHAVIOR UNDER AMBIENT TEMPERATURE VARIATION (REMUNOM, 2025)
Steel structures are usual for large spans buildings, as bridges and industrial sheds. Steel has a high thermal conductivity, so steel structures directly under weather conditions may suffer considerable temperature variation, and stresses associated to them. Engineers must define if these stesses consideration for design purposes is needed. This work analyzes compression stresses in beams under ambient temperature variation. Different sections, lenghts, temperature gradients and connections stiffnesses are evaluated. It was observed that connection stiffnesses have a remarkable influence in stresses magnitude. So, in beams with rigid connections, it may be needed the consideration of thermal stresses for design purposes.